The Role of Type 2 Diabetes Mellitus Education in Preventing Type 2 Diabetes Mellitus in Students of the Nutrition DIII Study Program Cirebon Tasikmalaya Polytechnic - Adiyaksa, Jongga; Vimala, Dewi; Sasi, Maheswari Adya; Rahmadina, Regita (Jurnal Indonesia Sosial Sains, 2025)
The International Diabetes Federation (IDF) reports that the global prevalence of type 2 diabetes mellitus (T2DM) was 9.3% in 2019, with projections indicating that the number of people affected will reach 578 million by 2030 and 700 million by 2045. Indonesia ranks seventh globally, with 10.7 million people living with diabetes—figures expected to rise to 13.7 million by 2030 and 16.6 million by 2045. West Java Province ranks 18th nationally based on diagnoses in populations aged ≥15 years. The purpose of this study is to examine the effectiveness of type 2 diabetes mellitus education in prevention efforts. This study employed a quantitative descriptive design to assess the impact of T2DM education on prevention among 77 nutrition students at Tasikmalaya Polytechnic, selected using Slovin’s formula with a 5% margin of error. Data were collected through structured questionnaires administered before and after the educational intervention, and analyzed using frequency distribution. Results revealed significant improvements in knowledge: prior to education, 53% of respondents demonstrated good knowledge, 44.1% adequate knowledge, and 2.9% poor knowledge. Following the intervention, 93.5% exhibited good knowledge, 6.5% adequate knowledge, and 0% poor knowledge—representing an increase of 31 respondents in the good knowledge category. The educational program was highly effective in enhancing students’ understanding of T2DM prevention. This improvement provides a vital foundation for fostering preventive health behaviors among future nutritionists, who will serve as health promoters in their communities. The findings offer implications for curriculum development, community health education initiatives, and long-term behavioral change strategies.